2010
DOI: 10.1088/0957-4484/21/34/345603
|View full text |Cite
|
Sign up to set email alerts
|

Single-step generation of fluorophore-encapsulated gold nanoparticle core–shell materials

Abstract: We report a simple route to produce fluorophore-encapsulated gold nanoparticles (AuNPs) in a single step under aqueous conditions using the fluorophore 1-pyrenemethylamine (PMA). Different amounts of PMA were used and the resulting core-shell gold nanoparticles were analyzed using UV-visible absorption spectroscopy, fluorescence spectroscopy, and transmission and scanning electron microscopy. Electron microscopy analysis shows nanoparticles consisting of a gold nanoparticle core which is encapsulated with a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Notably, addition of a large excess of honey, compared with Au(III), inverted the ratio of nanotriangles and nanospheres. Recently, a fluorophore-substituted amine 1-pyrenemethylamine acted as a strong coating agent for Au-NPs following an auto-reduction pathway based on the electrostatic interaction of the amine with the gold salt followed by a reduction process promoted by the protonated amine [99]. The authors clearly showed that the shell around the metal core of the particles was composed of unpolymerized 1-pyrenemethylamines.…”
Section: Organic Moleculesmentioning
confidence: 99%
“…Notably, addition of a large excess of honey, compared with Au(III), inverted the ratio of nanotriangles and nanospheres. Recently, a fluorophore-substituted amine 1-pyrenemethylamine acted as a strong coating agent for Au-NPs following an auto-reduction pathway based on the electrostatic interaction of the amine with the gold salt followed by a reduction process promoted by the protonated amine [99]. The authors clearly showed that the shell around the metal core of the particles was composed of unpolymerized 1-pyrenemethylamines.…”
Section: Organic Moleculesmentioning
confidence: 99%
“…29 The C 1s core level peak (Figure 3C) appearing at 285.2 eV is probably generated from the CNTs carbon (CC) at 284.6 eV, low levels of oxidized eV. 24,29,32 Therefore, XPS data suggests that an Au@THPP/ CNTs/AP composite combined by covalent linkage and Au@ THPP is surely attached on CNTs. Above all, Au@THPP/ CNTs/AP/ITO was accurately prepared, namely, a model has been successfully constructed by a chemical method.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…The interaction of the nanohybrid can be revealed by examining Au 4f photoelectron spectra (Figure B). The binding energies of the Au 4f peak core level are all at 83.9 and 88.0 eV, which is the gold 4f 7/2 (83.9 eV) and 4f 5/2 (88.0 eV), respectively. The line in 90.8 eV is probably the signal of gold oxide .…”
Section: Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations